Antibiotic and heavy metal sensitivity of Escherichia coli and Klebsiella pneumoniae isolated from different water sources of Cariri Cearense, Brazil (Research, Society and Development, 2020)
Resistance to antimicrobial agents and heavy metals results from the natural adaptation of the bacterial cell to environmental contaminants. Different bacterial strain sensitivity to water contaminants is still not well understood.  In the present study, we isolated Escherichia coli and Klebsiella pneumoniae strains from aquatic sources in the Salgado Basin in Ceara state, Brazil and, evaluated their sensitivity to antimicrobials and heavy metals. We identified and tested twelve bacterial strains for their sensitivity for copper and chromium using the broth microdilution method (0.49 - 250 μg / mL). We also tested the antimicrobials imipenem, meropenem, and ceftriaxone (0.25 - 128 μg / mL). Klebsiella pneumoniae was highly sensitive to imipenem and meropenem. Other strains, from a private water supply, were more resistant to ceftriaxone. Meropenem was the antimicrobial with higher sensitivity. Some strains of E. coli (collected from the water supply) are resistant to heavy metals.  K. pneumoniae strains showed enhanced tolerance for metals. Noteworthy, all strains of both species studied here have a minimum inhibitory concentration (for copper and chromium) lower than the values reported in the literature.  These results suggest that water-collected bacterial strains, sensitive to antimicrobials and heavy metals, is appropriate from the perspective of public health, however, require attention to the aquatic aquatic microbiota.